2007
DOI: 10.1097/qai.0b013e318030ff8e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Liver Fibrosis Progression and the Impact of Antiretroviral Therapy in HIV and Hepatitis C Coinfection Using a Noninvasive Marker

Abstract: The effects of highly active antiretroviral therapy (HAART) on progression of hepatic fibrosis in hepatitis C virus (HCV) coinfection with HIV are not well understood and are difficult to measure because of the need for repeated liver biopsy. We evaluated the evolution of a noninvasive measure of liver fibrosis, the alanine aspartyl transferase (AST)-to-platelet ratio index (APRI), longitudinally and determined its predictive value for hepatic outcomes in HIV-positive patients with and without HCV coinfection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 26 publications
8
50
2
1
Order By: Relevance
“…Although neither model had a high positive predictive value, the high negative predictive value of excluding advanced fibrosis was slightly better using FIB-4. Possible explanations for the discrepancies of the low PPV for advanced fibrosis between our findings and those of others [34,43] include different patient populations, including the large numbers of African-Americans in our study, different HAART regimens and alcohol use by coinfected patients that might have affected AST and ALT, the proportions with advanced fibrosis and steatosis, and the different laboratories used to determine AST, ALT, and platelet counts.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Although neither model had a high positive predictive value, the high negative predictive value of excluding advanced fibrosis was slightly better using FIB-4. Possible explanations for the discrepancies of the low PPV for advanced fibrosis between our findings and those of others [34,43] include different patient populations, including the large numbers of African-Americans in our study, different HAART regimens and alcohol use by coinfected patients that might have affected AST and ALT, the proportions with advanced fibrosis and steatosis, and the different laboratories used to determine AST, ALT, and platelet counts.…”
Section: Discussioncontrasting
confidence: 71%
“…Al-Mohri et al [43] demonstrated an AUROC of 0.847 for significant fibrosis in a co-infected cohort, with positive predictive value (PPV) of 100% for APRI [ 1.5 and 79% for APRI \ 0.5. In the original paper, a FIB-4 \ 1.45 had an NPV to exclude advanced fibrosis of 90% with a sensitivity of 70%, and a cutoff of [3.25 yielded a PPV of 65% and specificity of 97%.…”
Section: Discussionmentioning
confidence: 97%
“…For example, among HIVinfected patients starting ART in 13 cohorts in Europe, the USA and Canada, the overall crude death rate was 0.95/100 Source for Canadian population data: Canadian Human Mortality Database [14].…”
Section: <005mentioning
confidence: 99%
“…The aspartate aminotransferase (AST) to platelet ratio index (APRI) was used as a noninvasive surrogate for liver fibrosis and defined as: 100 ¥ (AST/upper limit of normal)/platelet count (10 9 /L) [13,14]. An APRI score > 1.5 was considered to indicate significant fibrosis (corresponding to a biopsy score > F2) [14]. ESLD included liver cirrhosis, ascites, hepatic encephalopathy, bleeding oesophageal varices, spontaneous bacterial peritonitis and hepatocellular carcinoma.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In our study, the duration of ART was the only factor independently associated with the presence of fibrosis based on FIB-4. The impact of ART on liver fibrosis is controversial, as highlighted by conflicting reports on worsening with long-term use of ART, especially didanosine or stavudine [9,31], absence of significant effect [22], or even improvement following commencement of PIs [32,33]. Furthermore, Mendeni et al followed a cohort of 1112 HIV-mono-infected patients for approximately 6 years and found that progression of fibrosis, assessed by APRI and FIB4, was prevented by viral control with early ART, provided that didanosine use was avoided [33].…”
Section: Discussionmentioning
confidence: 99%